PENGARUH KOORDINASI DAN DISIPLIN KERJA TERHADAP EFEKTIVITAS KERJA PEGAWAI PADA SEKRETARIAT DEWAN PERWAKILAN RAKYAT DAERAH (DPRD) KOTA BANDAR LAMPUNG - Haninun Haninun; Yeti Salviyana (e-JKPP, 2020)
The problems in this study are: (1) Does Coordination affect the Work Effectiveness of Employees at the Secretariat of the Regional Representative Council of Bandar Lampung City, (2) Does Work Discipline affect the Effectiveness of Employee Work at the Secretariat of the Regional Representative Council  of the City Bandar Lampung, (3) Does the Coordination and Discipline of work jointly influence the Work Effectiveness of Employees at the Secretariat of the Regional Representative Council  of Bandar Lampung City.The research method used in this study is the analytical survey method. This study aims to analyze the influence between the variables studied namely Coordination (X1), work discipline (X2), improving service quality (Y) in this study used quantitative research types to verify the research hypothesis. These methods and techniques were chosen because they allow a more extensive study of the influence of the research variablesThe results showed that Coordination had a significant effect on work effectiveness. The measurement of coordination dimensions, according to Guilford's criteria, is in the sufficient category. Then the Work Discipline affects the effectiveness of work in the Secretariat of the Bandar Lampung Regional Representative Council, or in other words that with adequate human resources will increase the effectiveness of work at the Secretariat of the Bandar Lampung Regional Representative Council, according to the criteria Guilford is in the sufficient category. Then the joint influence of Coordination and work discipline on work effectiveness At the Secretariat of the Regional House of Representatives  of Bandar Lampung City, according to Guilford's criteria is in the sufficient category, it occurs because the implementation of coordination by employees has not fully coordinated well between sections or coordination between leaders and subordinates and vice versa, then the ability of human resources is relatively not optimal.